SETD8 induces stemness and epithelial–mesenchymal transition of pancreatic cancer cells by regulating ROR1 expression. (2nd October 2021) - Liu, Mengqi; Shi, Yihua; Hu, Qiangsheng; Qin, Yi; Ji, Shunrong; Liu, Wensheng; Zhuo, Qifeng; Fan, Guixiong; Ye, Zeng; Song, Changfeng; Yu, Xianjun; Xu, Xiaowu; et al.
Abstract: Pancreatic cancer (PC) is one of the most deadly diseases, and its incidence is increasing year by year. The methyltransferase SETD8 has been demonstrated to play an important role in tumor cell proliferation and metastasis. However, little is known about whether SETD8 could affect the invasion and metastasis of PC and the mechanism underlying the regulation. Based on our previous report, here, we further found that SETD8 could promote the invasion and migration of PC cells by inducing the expression of receptor tyrosine kinase-like orphan receptor 1 (ROR1). ROR1 was predominantly upregulated in PC tissues and was correlated with lymph node metastasis and worse prognosis. Mechanistically, SETD8 mediated ROR1 activity and regulated PC cells invasion and migration, although promoting the expression of stemness and epithelial–mesenchymal transition-related molecules. This promotion effect disappeared when the catalytically inactive mutant SETD8 was overexpressed, which could be counteracted by the SETD8-specific methyltransferase inhibitor UNC0379. Collectively, our results demonstrate that SETD8 may be a novel prognostic factor and a therapeutic target of PC.